Histological and bacteriological changes in intestine of beluga (Huso huso) following ex vivo exposure to bacterial strains - Salma, Wahida; Zhou, Zhigang; Wang, Wenwan; Askarian, Fatemeh; Kousha, Armin; Ebrahimi, Maryam Tajabadi; Myklebust, Reidar; Ringø, Einar (Aquaculture, 2011)
In the present study the intestinal sac method (ex vivo) was used to evaluate the interactions between lactic acid bacteria and staphylococci in the gastrointestinal (GI) tract of beluga (Huso huso). The distal intestine (DI) of beluga was exposed ex vivo to Staphylococcus aureus, Leuconostoc mesenteroides and Lactobacillus plantarum. Histological changes following bacterial exposure were assessed by light and electron microscopy. Control samples and samples exposed only to L. mesenteroides and a combination of L. mesenteroides and S. aureus, had a similar appearance to intact intestinal mucosal epithelium, with no signs of cellular damage. However, the exposure of the DI to S. aureus and L. plantarum resulted in damaged epithelial cells and disorganised microvilli. Furthermore, 16S rDNA PCR denaturing gradient gel electrophoresis (PCR-DGGE) was used to investigate the adherent microbiota of distal beluga intestine. Several bacterial species were identified by DGGE in the present study that has not previously been identified in beluga.